Modelo 3-4-1 reduzido - Pinheiro, Paulo Rogerio Dias (2013)
We build a gauge model based on the SU(3)C ⊗ SU(4)L ⊗ U(1)X symmetry where the scalar spectrum needed to generate gauge boson and fermion masses is reduced to a lesser content than usually assumed in literature. In order to guarantee that such a reduction is self-consistent, we first show that the model possesses a Landau pole at the scale of few TeV. In fact, the scalar spectrum reduction is possible because the fermion masses that do not come from Yukawa interactions, can be suitably generated by effective operators, supressed by a few TeV scale instead of a too high energy scale (like Planck or usual grand unified theories scale). In this way we are able to keep only three scalar quartets out of the original four quartets and a decouplet, which are in the right amount to engender the spontaneous symmetry breaking of the model to the electroweak standard model and subsequently to the U(1)QED gauge group. This reduced spectrum enables a simpler framework when developing the phenomenology of such model.